Cidades, competição e planejamento: a reestruturação dos anos 1990 em São José do Rio Preto - SP - Petisco, Andréa Celeste de Araujo (2002)
"This study tries to understand how the sixties, have reflected on São José do Rio Preto's urban planning. Knowing the capitalism fitting through the production proccess, the work organization and distribution, the state role adjustment. It's related to the new world map and the cities new role in the global scenary, what drives to this work focus: Reconstruction of the local government, mainly related to the urban space management and their consequences on the urban structure. The work finishes when the new tendency of the urban planning are higlighted, it's called city strategist planning is São José do Rio Preto range."